The Council of Ministers and the problems of Russian Orthodox Church (1906–1914) - F. GAYDA (Vestnik Pravoslavnogo Svâto-Tihonovskogo Gumanitarnogo Universiteta: Seriâ II. Istoriâ, Istoriâ Russkoj Pravoslavnoj Cerkvi, 2014)
The article focuses on representations of the Russian government on the main problems of the Orthodox Church in the early twentieth century. The ﬁ rst Russian revolution of 1905-1907 led to the proclamation of the principle of freedom of conscience, which must be reconciled with the maintaining principle of the dominant Church. For political reasons, the government embarked on a search for union with the Old Believers, but the Church was against this trend. The procurator of the Holy Synod P. P. Izvolsky tried to defend its interests in the government, but rarely found support. Meanwhile, Stolypin`s government feared complications of their relationship with the Synod. The government originally set itself the task of fully implement all the principles of the decree 17 April 1905. The revival of parish life was the main task in the ﬁeld of Church according to the government. This problem was more urgent as political stability was realized. These particular problems are identiﬁed the appointment of V. C. Sabler to oﬃ ce of the procurator of the Holy Synod. Sabler adjusted its policies in the confrontation with the III State Duma. It castigated the Synod and the alleged abolition of parochial schools. Sabler drafted a reform of the parish, which unlike Izvolsky and Duma`s projects did not imagine electing clergy, moreover, he retained bishop`s control over the parish council. Sabler developed parish reform, but its implementation is complicated by the opposition of the executive and legislative powers. However Sabler could not get consent from the Council of Ministers in carrying out reforms parish bypassing legislative chambers. Policy of the Council of Ministers are supported by the monarch, who used his supreme power by the prime minister or the procurator only in special cases.